Quantitative easing, accounting and prudential frameworks, and bank lending - Andrea Orame; Rodney Ramcharan; Roberto Robatto (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
We study whether regulation that relies on historical cost accounting (HCA) rather than mark-to-market accounting (MMA) to insulate banks' net worth from financial market volatility affects the transmission of quantitative easing (QE) through the bank lending channel. Using detailed supervisory data from Italian banks and taking advantage of a change in accounting rules, we find that HCA makes banks significantly less responsive to QE than MMA. Hence, while HCA can insulate banks' balance sheets during periods of distress, it also weakens the effectiveness of unconventional monetary policy in reducing firms' credit constraints through the bank lending channel.
Keywords: G28; E52; M48; 330; Unconventional monetary policy; bank lending channel; sovereign default premia; regulatory capital; historical cost accounting